PENGARUH DIMENSI ETIKA, AKUNTABILITAS DAN TRANSPARANSI TERHADAP KUALITAS PELAYANAN PUBLIK DALAM PERSPEKTIF SOUND GOVERNANCE DI KANTOR SAMSAT KABUPATEN GOWA - Asrini Asrini; Sudarmi Sudarmi; Hafiz Elfiansya Parawu (Department of Public Administration, Muhammadiyah University of Makassar, 2019)
Public service has become one of the yardsticks and indicators that reveals whether or not the governance is soundly implemented in terms of the bureaucratic capacity. This is one of issues to deal with in Indonesia. The purpose of the study was to find out the effects of the dimensions of ethics, accountability and transparency on the quality of public services in the viewpoint of a sound governance perspective in the Samsat office of Gowa Regency. This study used descriptive quantitative research method. In deriving a sample, the sampling technique used was a saturation sampling comprising 36 employees and 36 people in the Samsat office of Gowa regency. The data obtained was analyzed using multiple linear regression. The results of the study showed that the dimensions of ethics, accountability and transparency on the quality of public services in the Samsat district of Gowa Regency were put in the